Tupperware Products-Perception of Users in Chandigarh - Sood, Smriti; Priyadarshini, Shabnam (Indian Journal of Marketing, 2004)
With the onset of liberalization, privatization and globalization, a revolutionary trend is reflected in the Indian homes. The changed family structure, increased number of working women and high disposable incomes has changed the lifestyle of the modern urban Indian. Paucity of time has set people looking for more convenient products. These help in maintaining a desired life style. Besides, an increasing consciousness about health and hygiene, status and right to pamper the self has also contributed to the change in the thought process with regard to spending the money earned and the aspired quality of life. Markets are flooded. The Consumer has a choice. Competition is continuously rising at all levels. Be it price, range, geographic spread, substitute and generic products, the clutter has become an uncomfortable din for the customer. All sellers are making special and unique attempts to stand out and seek attention of the consumer .The customer on the other hand has suddenly realized his status as the ’king’ driving the competition.